From public to digital spaces: Spatial and media practices of the 2017 'Unite Cyprus Now' peace protests. (August 2021) - Themistocleous, Christiana
Abstract: Cyprus is a divided country affected by long-term conflict between Greek-Cypriots and Turkish-Cypriots, but a meeting among key politicians in Switzerland in 2017 raised hopes that the 43-year division would come to an end. Ahead of this meeting, peace protests organised by Unite Cyprus Now (UCN) erupted in Nicosia urging politicians to find a solution. This study explores how the UCN protest signage was used during the demonstrations and how protesters' practices intersected across physical and digital spaces. Data was collected through an interview with a UCN peace activist, digital manifestations of the UCN protest signage online and a three-year ethnographic monitoring of the protest site. The data analysis, informed by Mediated Discourse Analysis, reveals that UCN's spatial and media practices supported activism work by enacting resistance, mobilising protests, sharing news from the ground, and circulating to local and global audiences counter-discourses of unity and peace. At the same time, social actors against the UCN initiative used the affordances of digital media to resemiotise the UCN protest signage, change its meaning and re-circulate hegemonic nationalist discourses.